IMMUNOMODULATORY OF Bifidobacterium breve AND INHIBITORY EFFECT OF BIFIDOBREVICIN -LHM ON Streptococcus agalactiae AND ITS β-HEMOLYSIN - H. Mahdi, L. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this research was production, purification and characterization of  Bifidobrevicin-LHM from  Bifidobacterium breve isolated  from women breast Colostrum. The antibacterial activity of crude and purified Bifidobrevicin-LHM on Streptococcus.agalactiae were assayed, also investigated their effect on β-hemolysin activity which is purified from S.agalactiae in vitro .We developed an untried mouse model of acute S.agalactae pneumonia, biochemical, histopathological, microbiological, innate and specific immune response were determined. Purified and  crude Bifidobrevicin-LHM exhibited bactericidal  action against S.agalactiae isolates and its  β-hemolysin activity in vitro. Oral and Intranasal administration of B. breve post infection leading to  significantly increase S.agalactae clearance rates in lung and blood, reduce the BAL albumin concentration,lung injury and Lactate dehydrogenase activity, enhanced production of Interleukein 10,IL-4 and high level of BAL -anti S.agalactiae IGg compared with control P